GILLNET FISHING GEAR ASSEMBLY MANAGEMENT FOR COASTAL FISHERMEN - Sullaida; Jamilah; Nurmala; Suhardanil; Yusril Riza Mahendra (RADJA PUBLIKA, 2023)
The success of fishing is influenced by several factors, namely knowledge about the fishing ground, fish behavior, fishing methods and techniques, and the fishing gear used. Gill nets (gill nets) are environmentally friendly fishing gear, protect marine habitats, and can be developed as fishing gear on a commercial scale. However, not all fishermen can make gill nets. Service activities are carried out aiming to provide education to fishermen in the form of activities to design, assemble, operate surface gill nets. Community service activities were carried out in Kampung Jawa, Banda Sakti District, North Aceh Regency using the Focus Group Discussion (FGD) method and demonstrations. Gillnet has good prospects to be developed as a commercial fishing gear because raw materials are easy to obtain and can be used independently or in groups. This community service activity shows a success rate of 96%, this is shown by the ability of coastal fishermen to easily make GillNet and to do it in groups. Every stage of community service activities can be followed properly, even fishermen hope that this activity can be continued by making other fishing gear. Through this activity, it is hoped that fishermen will have the knowledge, skills and attitudes in running capture fisheries entrepreneurship, especially gill nets, considering that gill net fishing gear has a great opportunity to be developed in the coastal area of Lhokseumawe City.